Maternal and Child Health Global Challenges, Programs, and Policies - Ehiri, John (Springer US : Imprint: Springer, 2009)
Maternal and Child Health: Global Challenges, Programs, and Policies Edited by John Ehiri, PhD, MPH, MSc (Econ.) Our current era of globalization, war, and socioeconomic unrest has revealed public health as a worldwide concern and a major frontier for social justice with maternal and child health at its epicenter. Yet, there has been a relative scarcity of textbooks specifically dedicated to this crucial area. Maternal and Child Health: Global Challenges, Programs, and Policies addresses this gap by analyzing the range of socioeconomic and environmental factors, health care disparities, politics, policies, and cultural practices that impact the health and safety of mothers, as well as the well-being and optimum development of their children. Individual sections focus on unequal distribution of the world's resources, politics and power, specific disease concerns, programs, policies and emerging concerns with a focus on what is currently being done, and what needs to be done to improve the health status of women, children, and adolescents. The book's contributors are some of the world's most respected experts, carefully selected to represent different global geographic regions and diverse professional disciplines related to maternal and child health from both academic and field practice perspectives. Among the topics in this authoritative volume: The impact of war, globalization, gender inequity, and harmful traditional practices (e.g., female genital mutilation). Specific health concerns, including tuberculosis, malaria, HIV, and malnutrition. Child and adolescent health issues, from abuse and neglect to children in difficult circumstances. Pregnancy-related issues: safety, abortion and post-abortion care, teen pregnancy, and more. Strategies for planning, developing, and maintaining maternal and child health systems in developing countries. The status of global initiatives, such as Integrated Management of Childhood Illnesses and the Millennium Development Goals. The status of evidence-based maternal and child health in the developing world. With such a wealth of information on both practical and conceptual levels, Maternal and Child Health: Global Challenges, Programs, and Policies is as relevant to students and researchers in the field as it is to policy makers and those working for global health and development organizations. Each chapter features discussion questions and learning objectives, making this book an excellent stand-alone text for courses in global health in general and global maternal and child health in particular.